2022
DOI: 10.3390/inventions7030070
|View full text |Cite
|
Sign up to set email alerts
|

Waste Plastic Direct Extrusion Hangprinter

Abstract: As the additive manufacturing industry grows, it is compounding the global plastic waste problem. Distributed recycling and additive manufacturing (DRAM) offers an economic solution to this challenge, but it has been relegated to either small-volume 3D printers (limiting waste recycling throughput) or expensive industrial machines (limiting accessibility and lateral scaling). To overcome these challenges, this paper provides proof-of-concept for a novel, open-source hybrid 3D printer that combines a low-cost h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Today's high-volume 3-D printers are expensive (e.g., The BOX Large by BLB Industries costs $298,000 [33] and even the open source offerings from re:3D of the Gigabot XLT cost $17,000 [34] . Recently, however, Petsiuk et al [35] demonstrated the potential to make a FGF/FPF large scale printer with a GigabotX extruder based on the open source cable driven Hangprinter concept [36] . This radically reduced the cost of large-scale printing below $5,000 and offers the potential to make an impact on GHG emissions be allowing large-scale recycled plastic waste printing at more accessible capital costs.…”
Section: Hardware In Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…Today's high-volume 3-D printers are expensive (e.g., The BOX Large by BLB Industries costs $298,000 [33] and even the open source offerings from re:3D of the Gigabot XLT cost $17,000 [34] . Recently, however, Petsiuk et al [35] demonstrated the potential to make a FGF/FPF large scale printer with a GigabotX extruder based on the open source cable driven Hangprinter concept [36] . This radically reduced the cost of large-scale printing below $5,000 and offers the potential to make an impact on GHG emissions be allowing large-scale recycled plastic waste printing at more accessible capital costs.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…can be classified as a redundantly actuated, 3°-of-freedom parallel cable driven robot (CDPR) [41] . Due to a frameless design, it is scalable and relatively low cost compared to large gantry machines making it an accessible solution for DRAM when coupled with the concept of FGF/FPF printing using recycled feedstock [35] . The Hangprinter consists of 4 local anchors (3 on the ground and 1 on ceiling), which control movement of the Hangprinter end effector in 4 local axes (A, B, C and D axis) shown in Fig.…”
Section: Hardware Descriptionmentioning
confidence: 99%
See 3 more Smart Citations